Mineralogical, Geochemical, and Mechanical Characteristics of Intrusive Andesite Rock Slope in Sangon 2 Area, Kulon Progo Regency, Indonesia - Hnin Thandar Phyu; Heru Hendrayana; I Gde Budi Indrawan; Toshitaka Kamai (Journal of Applied Geology, 2020)
This study was carried out to investigate mineralogical, geochemical, and mechanical characteristics of intrusive igneous rock andesite consisting of Sangon 2 Slope located in Kulon Progo Mountains. Mineralogical characteristics of the rocks consisting of the slope were identified by visual observation of hand specimens in the field and petrographic and X-ray Diffraction (XRD) analyses of the rock samples in the laboratory, which rock genetic classification was determined. Types of rock hydrothermal alterations were determined by the presence of key minerals identified in the petrographic and XRD analyses. Hydrothermal alteration intensity was determined by comparing the number of secondary minerals to the primary minerals observed in the petrographic analyses of thin sections by point counting method. Rock weathering degrees were determined in the field based on the visual characteristics and in the laboratory-based on the Chemical Index of Alteration (CIA) of the rock samples. The rock uniaxial compressive strength (UCS) was determined by point load and compression tests. The results showed that the rocks typically consisted of 6.37 to 74.3% plagioclase, 1.52 to 6.82% quartz, 7.81 to 17.2% hornblende, and 4.81% pyroxene minerals and, therefore, were classified as andesite. The presence of chlorite and calcite as secondary minerals in the andesite rock samples indicated that the parent andesite rocks had undergone prophylactic hydrothermal alteration. Meanwhile, the percentages of primary minerals to secondary minerals indicated that the andesite rocks had undergone weak to high alteration intensity. Based on the visual characteristics, the research area consisted of fresh, slightly, moderately, highly, and completely weathered andesite rocks, and residual soil. The CIA values of the rock samples increased with the increase in rock weathering degree. Rock weathering degrees identified by the visual characteristics appeared to be in good agreement with those classified based on the CIA. The lower part of the mine slope profile consisted of fresh and slightly and moderately weathered andesite rocks, which had relatively high strength and were classified as very strong rocks. Meanwhile, the upper part of the slope profile consisted of highly and completely weathered andesite rocks, which had low compressive strength.Keywords:  andesite, hydrothermal alteration, kulon progo,  prophylactic alteration, weathering